Application of the Student Facilitator and Explaining Model Assisted by Domino Media on Interest in Learning History - Muhammad Ikram; Pulung Sumantri; Imelda Megawati Gultom (CV. Rayyan Dwi Bharata, 2024)
Study This aim For apply a sparse learning model or not enough used by most teachers in schools, as for the model that has become focus researcher in study This is a Students Facilitator and Explanation learning model with with the help of domino media as the current media This exist among generation young Indonesians. As for the application of this model and media For see there is change interest Study history the original student still very low in class XI IPS at SMAN 1 Want Jaya. Study This background behind problem from exists problems faced by teachers when teach ie student No show joy moment learning, encouragement student For do activity in learning very low, students No own will or desire For solve problem in a way independent, they are not enough show exists involvement active and inclined passive like No There is will For move, and it turns out matter This refer to problem low interest Study seen history from indicators shown. In answering problems, researchers use approach quantitative with type Classroom Action Research, research action class done as effort in answer existing problems through stages systematic ie planning, implementation action class and observation. Implementation study taking place as many as 2 cycles, where cycle second is form refinement and evaluation from failure or shortages that occur in study cycle first, deep study this is what happened object study are teachers and students class XI IPS 1 SMAN 14 Medan, engineering analysis of the data used is using descriptive analysis techniques namely data obtained from observations teachers and students, as well as interview results will be analyzed descriptively. Assessment of student interest in learning will be calculated using the DP (Descriptive Percentage) formula by (Rukajat, 2018) . If score from results observation reach or exceeded the targets set determined, then interest Study student after the implementation of the student facilitator and explaining learning model assisted by domino media is stated increase. Next, the instrument used that is sheet teacher and student observations, as well documentation. Based on results study action classes that have been carried out on students class XI IPS 1 at SMAN 14 Medan in 2 cycles, obtained results namely in cycle I results related teacher observations The application of the student facilitator and explaining learning model assisted by domino media was 67% implemented, meanwhile increase interest Study students 63% in cycle I however Not yet fulfil indicator 80% success for teacher observation and 75% for interest Study students, so continued in cycle II. Implementability application of learning models student facilitator and explaining assisted by domino media By teachers 93%, meanwhile increase interest Study 80% of students in Cycle II showed increase has fulfil indicator success that has been set. So that application of the student facilitator and explaining learning model assisted by domino media increase interest Study student class XI IPS 1 SMAN 14 Medan.